Labor dispute settlement and decision making - Sale, Jonathan P. (Philippine Journal of Labor and Industrial Relations, 2005)
Exploring the various methods of labor dispute settlement and decision making and their efficacy and effectiveness in achieving the goals of public policy is at the core of Jonathan Sale's paper. He explores the hypothesis stating that industrial peace is a function of efficacious dispute settlement mechanisms which in turn are a function of decisions based on the logic of appropriateness. In this light, Sale finds that utilization by labor and employer of legalistic and non-cooperatives mechanisms is increasing while use of consent based and cooperative mechanisms is declining, signifying that labor and employer tend to advance rational self-interest rather than exhibit appropriate decision behavior based on trust and reciprocity. Sale also discusses how decision theory can help guide "the authoritative allocation of public goods."